2018
DOI: 10.1186/s13063-018-2716-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress following a motor vehicle crash: preliminary results of a randomised controlled trial investigating brief psychological interventions

Abstract: BackgroundThe preliminary results of a randomised controlled trial are presented. The aim of the trial is to determine the efficacy, feasibility and acceptability of email-delivered psychological interventions with telephone support, for adults injured in a motor vehicle crash engaged in seeking compensation. The primary intention for this preliminary analysis was to investigate those who were psychologically distressed and to stop the trial midway to evaluate whether the safety endpoints were necessary.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The trials were published between 1963 and 2021. Most trials concerned the treatment of adults with either an anxiety disorder 24,28,29,40 or a depressive disorder, 22,23,[35][36][37][38][39][40][41] with the remaining four aimed at treating adults with schizophrenia or a related disorder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trials were published between 1963 and 2021. Most trials concerned the treatment of adults with either an anxiety disorder 24,28,29,40 or a depressive disorder, 22,23,[35][36][37][38][39][40][41] with the remaining four aimed at treating adults with schizophrenia or a related disorder.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for exclusion were not having a placebo group, not having a passive group studies analysing a singular non‐persistent outcome and studies with a healthy group. Characteristics and quality of the 24 articles (1244 participants: only control groups) included in systematic review, of which 21 were included for meta‐analysis are shown in Table 1 21‐44 . The trials were published between 1963 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation